Minds in (En)action: The Phenomenon of Cognition From an Evolutionary and Ecological Standpoint (Nóema, 2021)
This paper examines cognitive processes from an evolutionary, ecological and systemic perspective. Starting from Darwinian theory and the development of Extended Evolutionary Synthesis, the reference to evolutionary biology allows a rethinking of minds as complex phenomena "at the crossroads" between organisms (and their structures) and the environments they inhabit and contribute to build. It is proposed that this vision opens a space to overcome philosophical traditions that see in the minds "things" and in cognition a mirroring or representation of the world, to come to an understanding of the former in terms of complex systems and to interpret the latter through the concept of "enaction".
Keywords: Representation; Cognition; Evolution; Extended Synthesis; Complexity; Niche construction; Enaction; Mind-system